Peran Lingkungan Sosial dalam Mengatasi Fenomena Quarter Life Crisis pada Mahasiswa Generasi Z di Perguruan Tinggi - Setiagils, Ananda; Abdul Rozak; Neng Sri Nuraeni (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
This research aims to: 1) Understand the strategies and mechanisms used by Generation Z students in overcoming the Quarter Life Crisis phenomenon, 2) Examining the role of the social environment in helping Generation Z students overcome the Quarter Life Crisis, 3) Identifying the impact of the Quarter Life Crisis phenomenon on the daily lives of Generation Z students, and 4) Analyzing the obstacles faced by Generation Z students in overcoming the Quarter Life Crisis. The research method used is a descriptive qualitative method. The sampling method used in this research was purposive sampling, with 12 respondents. Research data was collected by interviews and documentation. The data validation technique used is source triangulation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The research results show: 1) Generation Z students develop various strategies to overcome the Quarter Life Crisis which involve identifying life goals, making decisions, and maintaining social relationships, 2) The social environment has an important role in helping Generation Z students overcome the Quarter Life Crisis, 3) The impact of the Quarter Life Crisis on daily life includes feelings of being trapped in a monotonous routine and without direction, and 4) Obstacles in overcoming the Quarter Life Crisis come from certain goals of parents, perceptions of the social environment, and difficulties in adapting to new environments.